A exploração do trabalho durante a ditadura empresarial-militar no Brasil: uma proposta de aula oficina no ensino de História - Silva, Carlos Augusto da (2025)
This research focused on the exploitation of labor during the period of the corporate-military dictatorship in Brazil. The main objective was to conduct a workshop-style History class to introduce the theme of labor exploitation under the regime into classroom discussions. The investigation unfolded through the following specific objectives: to explore, by means of the digital tool of podcasts, the historical learning of high school students regarding the subject; and to examine, within the scope of the History workshop, the reception of a report instrument with questions answered by students, based on the analysis of episodes from the podcast História em Meia Hora and reports from the website Agência Pública about companies complicit with the dictatorship. The research was guided by the following question: why is there a predominant way of teaching the military dictatorship in History classes that emphasizes the repression of individual rights while, to some extent, obscuring social rights and the exploitation of workers? The workshop methodology developed by Isabel Barca (2004) served as the foundation for this research, in dialogue with key concepts that underpin History teaching, such as “historical learning,” “historical literacy,” and “historical consciousness.” Four report instruments were analyzed, applied to students in the 2nd year (2023) and 3rd year (2024) of high school, in order to assess whether the answers demonstrated understanding of concepts such as “historical source,” “substantive concepts,” and “second-order concepts,” as well as students’ perceptions of “historical consciousness.” The findings indicate that these ideas were indeed assimilated by the students. As a final product, a workshop-style class (Barca, 2004) was developed, addressing the theme of the corporate-military dictatorship.